Fast analysis of anabolic steroids in urine samples by electrospray ionization tandem mass spectrometry - Chang, YS; Jang, JS; Chung, BC (MARCEL DEKKER INC, 1996)
Unauthorized steroids were administered to volunteers and the presence of anabolic steroids in urine samples were directly confirmed by electrospray ionization mass spectrometry without using the prerequisite steps of enzymatic hydrolysis and trimethylchlorosilane derivatization. Further structure determination has been conducted by collisionally induced dissociation in a triple quadrupole tandem mass spectrometer. Overall, the electrospray ionization and tandem mass spectrometry methods prove to be simple, fast and sensitive for the analysis of anabolic steroids in urine samples.